Institutional experience of surgical management of intramedullary spinal cord tumours - Singh Naik, B. D. Bharath; Prasad, Kadali Satyavara; Thota, Phaneeswar; B. V. S., Raman (International Journal of Research in Medical Sciences, 2017)
Background: Intramedullary spinal cord tumors are rare entity accounting for only 5-6% of all central nervous system tumors. Much literature is not available regarding these tumors owing to their rarity. Present study includes 24 cases of intramedullary spinal cord tumors with pain and progressive weakness. Radiological evaluation showed various intramedullary lesions like ependymoma, astrocytoma, epidermoid etc. spreading over various levels of spinal cord like cervicomedullary, cervicodorsal and dorsal cords. Methods: The study included all the cases admitted with intramedullary spinal cord tumors in neurosurgery ward in King George hospital, Visakhapatnam, Andhra Pradesh, India during a period of three years from 2014 to 2016. Clinical profile of the patients was analyzed for the clinical presentation, age and sex distribution, histopathological study, pre-and postoperative neurological status, complications and functional outcome. All the patients are followed for a period of 6months to 3years. Results: Of the 24 cases, most common age group was second (7 patients) and third (7 patients) decades which is upto 29.16% each. Males (16 patients) are more affected than females in 66.66%. Ependymoma is the most common tumor seen in 41.66% (10 patients) followed by astrocytoma in 33.33% (8 patients). The surgical technique, extent of resection, pre and postoperative neurological status and functional outcome are discussed. Conclusions: Intramedullary tumours occur commonly among males in the 2nd to 4th decades. Among the intramedullary tumours ependymoma from the commonest lesion subtypes. Most common location is cervical cord segment. Ependymomas have a good plane of cleavage and are thus amenable to radical excision. Patients with good Mc Cormicks grade in pre-operative stage are more amenable for total or near total excision. Prognostic factors affecting outcome are the preoperative neurological status, the plane of cleavage, the extent of resection, the nature and subtype of the lesion. With the improvement in microsurgical techniques and novel adjunctive like MRI, CUSA and intraoperative neurophysiological monitoring, surgery for intramedullary lesions can be carried out with acceptable morbidity and mortality.